2021
DOI: 10.1111/dth.14954
|View full text |Cite
|
Sign up to set email alerts
|

Association between surgical excision margins and outcomes in patients with dermatofibrosarcoma protuberans: A meta‐analysis

Abstract: Dermatofibrosarcoma protuberans (DFSP) is a tumor with low-grade malignancy and high recurrence rates. Wide local excision (WLE) is essential for DFSP, but its surgical excision margin is controversial. This study aimed to examine whether resection margin is associated with the prognosis of patients with DFSP by systematically reviewing related literature. Studies that evaluated the relationship between excision margins and outcomes after WLE were retrieved from the Cochrane Library, PubMed, Embase, and Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…In addition, the tumors in our practice settings are large as in most cases reported in the African literature 6,17,30 . Also, the dermatofibrosarcoma of Darier and Ferrand is known to have macroscopically invisible filiform pseudopodia that may extend several centimeters beyond the palpable limit of the tumor 17,24 . All these reasons explain why in our series, the resections were wide and deep.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In addition, the tumors in our practice settings are large as in most cases reported in the African literature 6,17,30 . Also, the dermatofibrosarcoma of Darier and Ferrand is known to have macroscopically invisible filiform pseudopodia that may extend several centimeters beyond the palpable limit of the tumor 17,24 . All these reasons explain why in our series, the resections were wide and deep.…”
Section: Discussionmentioning
confidence: 68%
“…6,17,30 Also, the dermatofibrosarcoma of Darier and Ferrand is known to have macroscopically invisible filiform pseudopodia that may extend several centimeters beyond the palpable limit of the tumor. 17,24 All these reasons explain why in our series, the resections were wide and deep. These large resections are corollary to large wounds that cannot be covered by direct skin suture.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A previous meta-analysis revealed that WLE with a 4 cm surgical margin provides 95% tumor clearance [ 124 ]. Another meta-analysis of eight observational studies revealed a significant positive correlation between a margin of more than 3 cm and the LRR and positive surgical margin rate [ 125 ]. However, the larger the surgical margin is, the more significant the cosmetic and functional problems that develop after WLE may be [ 126 ].…”
Section: Surgical Margin Of Primary Tumorsmentioning
confidence: 99%
“…Jelena Jeremic et al(16) reported a 55 years old female diagnosed as DFSP with nodular lesion 18x10cm. It was indicated by previous reports that excision margin less than 3cm increased recurrence(17).Charlotte Van Lee et al(18) indicated that the experience of surgeon, subcutaneous tentacle-like invasion and the symmetrical manner disease center contribute to high recurrence of DFSP. Xiong et al(19) reported the diameter of DFSP over 3cm maybe the risk factor of recurrence even though the statistical result did not show statistical signi cance.…”
mentioning
confidence: 93%